Continuing Professional Development ( CPD ) and Vocational Education and Training ( VET ) in Periodontology and Implant Dentistry - Meyle, Joerg; Lambert, France; Winning, Lewis; Bertl, Kristina; Bruckmann, Corinna; Biosse Duplan, Martin; Harrison, Peter; Laleman, Isabelle; Mattheos, Nikos; Molina, Ana; Stavropoulos, Andreas; de Waal, Yvonne C. M.; et al. (My University, 2024)
Aim: To (i) evaluate structured postgraduate part-time programs in periodontology, including those addressing peri-implant diseases, among members of the European Federation of Periodontology (EFP), (ii) the impact of the 2018 classification scheme and EFP clinical practice guidelines and (iii) propose a framework for periodontal vocational education and training. Materials and Methods: A summary of relevant European guidelines for vocational education and training was compiled. In a survey and in a systematic review, current part-time programs in continuing professional education in periodontology as well as in prevention and management of peri-implant diseases were examined. The implementation and dissemination of the 2018 classification scheme and the EFP clinical practice guidelines were assessed by literature analysis. Based on these findings, a framework for periodontal vocational education and training was generated. Results: Part-time programs for professional development in periodontology are established in nine EFP member countries. The systematic review identified lack of knowledge in prevention and management of peri-implant diseases among dental practitioners and hygienists. Continuing professional development was found to be important for education in prevention, classification and management of periodontal as well as peri-implant diseases. The proposed European framework consists of an escalator model with three levels (certificate, diploma and master). Discussion: Considering the identified variation in the national programs, there is a need to improve education in periodontal and peri-implant diseases. The proposed framework will help harmonize the national structures. Conclusion: The proposed framework for part-time professional development is expected to enhance professional qualification.
Keywords: ddc:610